The role of magnetic resonance imaging in acute abdominal pain in paediatric age group - Vijinder Arora; Tanveen Kaur; Kunwarpal Singh (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background The purpose of this study is to evaluate the utility of magnetic resonance imaging in the assessment of acute atraumatic abdominal pain as the first line cross sectional modality in children, so as to prevent excessive radiation exposure from computed tomography scan and to review the magnetic resonance imaging features of common acute abdominal and pelvic conditions. Results 30 patients (0–18 years) underwent rapid unenhanced magnetic resonance imaging. The results of our study indicated that for the diagnosis of causes for acute abdominal pain, magnetic resonance imaging had sensitivity of 92% (95% confidence interval 73.8–97.6%) and a specificity of 80% (95% confidence interval 28.4–99.5%). The positive predictive value was 95.8% (95% confidence interval 79.9–99.3%) and negative predictive value was 67% (95% confidence interval 33.1–89.0%) which had a highly significant statistical association (p < 0.001). Conclusion Unenhanced magnetic resonance imaging is an excellent option for the initial, detailed evaluation of acute abdominal emergencies in pediatric patients because it can diagnose the whole range of presenting abnormalities which include the causes of abdominal pain warranting surgical and nonsurgical management.